PLANNING OF MULTIPLE FEEDERS ELECTRICAL DISTRIBUTION SYSTEM - NORDIN, AHMAD SOLLEHIN (Universiti Teknologi Petronas, 2011)
ectrical Distribution System is a system to distribute electricity to users. Electricity that is being distributed comes from generation station where the electrical power is generated. The electrical power is then being transmitted through Transmission System to substations to be distributed to the users. Electrical Distribution System is very important because it affects the end users directly, thus distribution system planning is very essential. In general, distribution system planning process involves selecting the location of the substation, configuring how the substation connects with all the nodes, and selecting the conductor to be used as feeder for all the branches in the distribution system. In this project, several algorithms are implemented to design an electrical distribution system which are (1) Optimal Feeder Path Algorithm, (2) Modified Load Flow Algorithm, (3) Optimal Branch Conductor Selection Algorithm, and ( 4) Optimal Location of Substation Algorithm. These four algorithms are combined together to design a distribution system which provides high node voltages, low real and reactive power losses of branches, and low installation and operating costs. Three types of design are considered in this project, ( 1) single feeder distribution system, (2) two feeders distribution system, (3) three feeders distribution system.